A case study of applying scrum in teaching computer programming - Nguyen, Cong Danh (Đại học Quốc gia Hà Nội, 2020)
Teaching and learning computer programming have introduced many challenges to both lecturers and students in Computer Science. Objective: This paper presents a new computer programming teaching method. Method: Based on Scrum software development method, students in a computer programming course are divided into multiple teams. Scrum emphasizes effective collaboration and communication between students within their team to complete a list of required programming exercises. The students are encouraged to find out and share their solution with the team in order to gain more experience. Results: A case study that describes in detail an experiment in a first-year computer programming course is conducted to verify the benefits of the proposed method in terms of the improvement in students’ learning performance and attitude toward learning computer programming and to provide lessons learned.